Risk of Dengue Transmission in Cocody (Abidjan, Ivory Coast) - Diakarida Fofana; Jean Michel Vianney Beugré; Genevieve Lydie Yao-Acapovi; Sevidzem Silas Lendzele (Journal of Parasitology Research)
In recent years, an upsurge of vector-borne diseases has been reported in several parts of the world. Among these is dengue fever, the first arbovirus transmitted by mosquitoes of the genus Aedes. After the detection of the dengue virus serological types (type 1, 2, and 3) in the health district of Cocody-Bingerville in Ivory Coast, entomological investigations were carried out in the city of Cocody (host of most cases) to evaluate the risk of transmission of the disease in view of an effective vector control. Larval prospection together with the pitching of emergence traps was carried out in Caféier 5, Sideci-Coteau, Danga, Ecole de police, Gobelet village, Laurier 9, Lemania, Perles, 7ème tranche, and 12ème arrondissement. Entomological prospections revealed the predominance of Aedes aegypti (97.38%) as the main vector species of dengue viruses in Cocody. The Kruskall-Wallis test showed no statistically significant difference (KW = 1.8, p = 0.407) in the proportions of the vector species collected from the sampled sites. The risk of an outbreak of dengue fever in Cocody and other municipalities in the city of Abidjan is very certain insofar as the larval epidemic risk indices (Habitat Index, HI = 70.9; Container Index, CI = 40.26; and Breteau Index, BI= 21.3) reflect a very high epidemic risk (4 to 9) on the WHO density scale. The occurrence of Aedes aegypti in Cocody indicates the risk of transmission of the Dengue fever virus.